The Effect of Work–Family Conflict and Family–Work Conflict on Job Satisfaction with Work–Life Balance as a Mediating Variable at PT. Wahyu Wisata Mandalika - Maya Okyantari; Mukmin Suryatni (Danadyaksa: Post Modern Economy Journal, 2026)
This study examines the effects of Work–Family Conflict and Family–Work Conflict on Job Satisfaction, with Work–Life Balance as a mediating variable among employees of PT. Wahyu Wisata Mandalika. Using a quantitative approach, data were collected from 58 employees through simple random sampling and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The measurement model demonstrates satisfactory validity and reliability, while the structural model shows moderate explanatory power (R² = 0.463 for Work–Life Balance and R² = 0.488 for Job Satisfaction) and predictive relevance (Q² = 0.387). The findings reveal that both Work–Family Conflict and Family–Work Conflict negatively and significantly affect Work–Life Balance and Job Satisfaction, whereas Work–Life Balance positively and significantly influences Job Satisfaction. Furthermore, Work–Life Balance is confirmed as a significant mediating variable, indicating that role conflict reduces job satisfaction both directly and indirectly through decreased balance. This study contributes to the literature by extending role conflict and work–life balance frameworks through an integrated mediation model in the tourism sector, demonstrating that Work–Life Balance serves as a critical psychological mechanism linking dual-direction role conflict to job satisfaction in high-intensity service environments.